2021
DOI: 10.1155/2021/6668249
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion Protects Dopaminergic Neurons in Parkinson’s Disease through Antiferroptosis

Abstract: Ferroptosis is associated with neural degeneration of dopaminergic neurons in Parkinson’s disease (PD). However, how to control the level of ferroptosis in PD remains unclear. Clinically, moxibustion has been used to treat PD and has an apparent therapeutic effect on improving the motor symptoms of PD. In the present study, the PD rat model was constructed by two-point stereotactic 6-hydroxydopamine injection. Then, moxibustion was used to treat the PD rats. The expression of glutathione peroxidase 4 (GPX4) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Exceptionally, downregulation of tpi1b , fth1a , and maff was observed in both cell types after 0.5 μg/L BPF exposure (Figure c). The decrease in the expression of fth1a , a downstream target of Nfe2l2, across cell types indicates extensive oxidative damage in neurons. , This finding reveals another upstream regulatory role of microglia (where nfe2l2 expression was significantly decreased) in mediating neuron damage induced by BPF. After 5.0 μg/L BPF exposure, the transcription of genes related to neuronal morphology and dysmyelination was affected in both inhibitory and excitatory neurons, which might be associated with the abnormal endocytosis of microglia.…”
Section: Discussionmentioning
confidence: 78%
“…Exceptionally, downregulation of tpi1b , fth1a , and maff was observed in both cell types after 0.5 μg/L BPF exposure (Figure c). The decrease in the expression of fth1a , a downstream target of Nfe2l2, across cell types indicates extensive oxidative damage in neurons. , This finding reveals another upstream regulatory role of microglia (where nfe2l2 expression was significantly decreased) in mediating neuron damage induced by BPF. After 5.0 μg/L BPF exposure, the transcription of genes related to neuronal morphology and dysmyelination was affected in both inhibitory and excitatory neurons, which might be associated with the abnormal endocytosis of microglia.…”
Section: Discussionmentioning
confidence: 78%
“…MiR-335 enhanced ferroptosis by degrading FTH1 in in vitro and in vivo models of PD [156]. Moxibustion presents a neuroprotective function via anti-ferroptosis in PD [157,158]. Ferritinophagy-mediated ferroptosis involves in paraquat-induced neurotoxicity in PD [159].…”
Section: Parkinson's Diseasementioning
confidence: 98%
“…39 In addition, Huang and colleagues have revealed that moxibustion, a Chinese traditional external therapy, may inhibit ferroptosis and alleviate mitochondrial damage, ultimately improving DN (dopaminergic neuron) survival in PD rats. 40 Do Van et al have indicated that ferroptosis, as a cell death regulating mechanism, is essential for DN death and can be activated by PKCα, which subsequently initiates MEK in a RAS-independent manner. 41 As the mechanism by which ferroptosis regulates DN death is being explored, it has been discovered that ferroptosis initiated by 6-hydroxydopamine (6-OHDA) is inhibited via the p62-Keap1-Nrf2 pathway, suggesting it may be a potential therapeutic target for PD treatment.…”
Section: Ferroptosis and Dopaminergicmentioning
confidence: 99%
“…Professor Wang and his team have found that ferroptosis induced by paraquat and maneb is associated with the activation of NADPH oxidase in SHSY5Y dopaminergic cells and that NADPH oxidase inhibitors could reverse this process . In addition, Huang and colleagues have revealed that moxibustion, a Chinese traditional external therapy, may inhibit ferroptosis and alleviate mitochondrial damage, ultimately improving DN (dopaminergic neuron) survival in PD rats . Do Van et al have indicated that ferroptosis, as a cell death regulating mechanism, is essential for DN death and can be activated by PKCα, which subsequently initiates MEK in a RAS-independent manner .…”
Section: Ferroptosis In Neurodegenerative Diseasesmentioning
confidence: 99%